Posterior Tibial Tendon Tendovaginitis to Insufficiency: A Historical and Anatomical Review - James P Henry; James E Henry (Journal of Foot and Ankle Surgery (Asia Pacific))
Tenosynovitis was first described by Velpeau in 1818. Many others, including de Quervain in 1895, have noted the importance of this common condition and the painful symptoms associated with this pathology around the ankle. In 1936, Dr Kulowski of St Joseph’s, Missouri, was the first to publish on posterior tibial tendon (PTT) tendovaginitis (tenosynovitis). Since his initial description of the pathology, the condition has evolved into a complex spectrum of disease termed PTT insufficiency (PTTI). PTTI is the most common cause of adult-acquired flatfoot deformity (AAFD) and affects an estimated 3–10% of the population. The exact etiology of the condition remains unknown.